Smallpox vaccination: an early start of modern medicine in America - Dan Liebowitz (Greater Baltimore Medical Center, 2017)
Smallpox was eradicated by the World Health Organization in 1980. Before its eradication thedisease had a mortality rate upwards of 50% and had a significant impact on society. During theAmerican Revolutionary war, smallpox outbreaks were impeding the American war effort until1777 when George Washington carried out a mass inoculation campaign in the ContinentalArmy that reduced the mortality from smallpox to less than 2%. Inoculation was an early formof vaccination that used live virus from active pustules to induce a milder, but still sometimesdeadly, case of disease. Washington has been credited with helping to ease the burden ofsmallpox on the Army which improved the odds of success against the British. When EdwardJenner's vaccine reached America it was more readily accepted by political and medical leadersdue the success of Washington's inoculation campaign. The Founding Fathers argued thatsmallpox vaccination was the greatest discovery in modern medicine and they were likely correctthat it helped to usher in the modern era of vaccinology.